Formulasi Trilogi Dakwah KH Marzuki Mustamar Dalam Moderasi Beragama Sebagai Upaya Menjaga Keutuhan Umat - Siti As Syfa Aini; Ahmad Abdul Hadi Abdul Jawad Filfil (Mawaizh : Jurnal Dakwah dan Pengembangan Sosial Kemanusiaan, 2023)
The emergence of the phenomenon of inclusive da'wah in the era of globalization has triggered a harsh da'wah model and using religion as fiqh siyasah makes preachers in the current era tend to be easy to claim heresy and provocation. The focus of this research is to answer the concept of the KH. Marzuki Mustamar da'wah trilogy. Marzuki Mustamar and his contribution as an effort to maintain the welfare of the people through the moral message of da'wah conveyed. The type of research used in this study is a type of qualitative research with library research methods and approaches related to the theory of washi lah da'wah about the concept of moderate da'wah. The results of this study state that the welfare of the people can be built through the cultivation of the concept of Ahlu al-Sunnah Wa al-Jama>'ah creed and love for the homeland and acculturation between religion and local culture of the community, which in its values means that first, religion must be based on principles in a middle line (moderate); Second, the cultivation of the spirit of nationalism and tolerance between religious communities; third, concern for the preservation of local culture within the community. This research is expected to be able to answer the problems of the integrity of the people and be able to contribute to the empowerment of the people through the way of da'wah.